Daily volume, intraday and overnight returns for volatility prediction: Profitability or accuracy? - Fuertes, Ana Maria; Kalotychou, Elena; Todorovic, Natasa (My University, 2014)
This article presents a comprehensive analysis of the relative ability of three information sets—daily trading volume, intraday returns and overnight returns—to predict equity volatility. We investigate the extent to which statistical accuracy of one-day-ahead forecasts translates into economic gains for technical traders. Various profitability criteria and utility-based switching fees indicate that the largest gains stem from combining historical daily returns with volume information. Using common statistical loss functions, the largest degree of predictive power is found instead in intraday returns. Our analysis thus reinforces the view that statistical significance does not have a direct mapping onto economic value. As a byproduct, we show that buying the stock when the forecasted volatility is extremely high appears largely profitable, suggesting a strong return-risk relationship in turbulent conditions.
Keywords: Directional change prediction; Trading rules; Realized volatility; Conditional variance forecasting